1996
DOI: 10.1002/anie.199618381
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of a Circular Double Helicate

Abstract: Dedicated to Professor Guy Ourisson on the occasion of his 70th hirtlidaj.Helicates, metal complexes that form double" -41 or triple in solution and/or in the solid state, are generated by self-assembly of two or three ligand strands around suitable metal ions. Whereas the double helix of DNA results from the assembly of two complementary chains of nucleotides through hydrogen bonding, helicates form spontaneously from linear ligands composed of a series of discrete binding subunits through metal ion coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
294
0
14

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 632 publications
(312 citation statements)
references
References 31 publications
4
294
0
14
Order By: Relevance
“…A large number of low-molecular-weight molecules are obviously needed to create assemblies on the scale of macromolecules, approximately 10 4 -10 7 Da. Current synthetic strategies to create very large controlled assemblies are inspired by previous examples of smaller systems, such as melamine-cyanurate spheres (Whitesides et al 1991(Whitesides et al , 1995 (diameter approximately 2.5 nm) and helicates (Koert et al 1990;Hasenknopf et al 1996Hasenknopf et al , 1997. While these structures did not display any particular function, they established an important principle that small molecules can self-assemble into well-defined structures.…”
Section: Supramolecular Self-assembly At the Macromolecular Scalementioning
confidence: 99%
“…A large number of low-molecular-weight molecules are obviously needed to create assemblies on the scale of macromolecules, approximately 10 4 -10 7 Da. Current synthetic strategies to create very large controlled assemblies are inspired by previous examples of smaller systems, such as melamine-cyanurate spheres (Whitesides et al 1991(Whitesides et al , 1995 (diameter approximately 2.5 nm) and helicates (Koert et al 1990;Hasenknopf et al 1996Hasenknopf et al , 1997. While these structures did not display any particular function, they established an important principle that small molecules can self-assemble into well-defined structures.…”
Section: Supramolecular Self-assembly At the Macromolecular Scalementioning
confidence: 99%
“…Although other syntheses of trefoil knots have been reported [15][16][17][18][19][20][21][22] (as have composites of trefoil knots 23 and other molecular topologies such as catenanes [24][25][26][27][28] and Borromean links 29 ), higher-order molecular knots remain elusive. Here, we report on the synthesis of a molecular pentafoil knot that combines the use of metal helicates to create crossover points 30 , anion template assembly to form a cyclic array of the correct size [31][32][33] , and the joining of the metal complexes by reversible imine bond formation 34-37 aided by the gauche effect 38 to make the continuous 160-atom-long covalent backbone of the most complex non-DNA molecular knot prepared to date.So far, attempts to make molecular knots with more than three crossing points by extending the linear helicate strategy of Sauvage to ligands with more coordination sites have proved unsuccessful 30 , probably because joining the ends of each strand with the required connectivity becomes increasingly difficult as helicate length increases. An alternative way to use helicates (which generate the necessary crossing points) to make higher-order topologies could be to use cyclic structures or grids, where there is no requirement for there to be long distances between the ends of the strands that are to be connected.…”
mentioning
confidence: 99%
“…An alternative way to use helicates (which generate the necessary crossing points) to make higher-order topologies could be to use cyclic structures or grids, where there is no requirement for there to be long distances between the ends of the strands that are to be connected. To generate the five crossing points required for a pentafoil knot, we modified a motif for generating cyclic metal helicates discovered by Lehn in the mid-1990s [31][32][33] . Lehn found that double-stranded circular helicates of various sizes could be obtained using Fe(II) or Ni(II) ions with tris(bipyridine) ligands with very short inter-bipyridine spacers that destabilized the normally preferred three-metal-ion linear triple helicate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Less attention has been paid to producing self-assembled 'supermolecules' capable of performing a function such as binding a 'third-party' guest species. Recently, very elegant examples of self-assembled receptors capable of binding anions have been reported by Lehn and coworkers [2] and Stoddart et al [3].…”
Section: Introductionmentioning
confidence: 99%